1992
DOI: 10.1046/j.1365-313x.1992.t01-2-00999.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of a tobacco lipid transfer protein gene within the shoot apex

Abstract: SummaryA genomic clone coding for a putative lipid transfer protein was isolated from Nicotiana tabacurn. The gene is expressed in all aerial organs of the tobacco plant, with expression being highest in the upper part of the plant and declining towards the base (i.e. with increasing age). In the shoot apex transcript levels are highest in the LI layer, lower in the underlying cell layers, and are again higher in the submeristem region. This pattern is markedly different from those previously described for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…The conserved regions are boxed. C. Alignment of the deduced amino acid sequence of SDi-9 with other members of the LTP family, GLTPl from Gerbera hybrida [29], LPTl from Nicotiana tabacum [14], LTP from spinach 151 and PLTP from maize [40]. Both amino acid sequence identity and homology with SDi-9 protein are indicated in brackets at the end of each sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved regions are boxed. C. Alignment of the deduced amino acid sequence of SDi-9 with other members of the LTP family, GLTPl from Gerbera hybrida [29], LPTl from Nicotiana tabacum [14], LTP from spinach 151 and PLTP from maize [40]. Both amino acid sequence identity and homology with SDi-9 protein are indicated in brackets at the end of each sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of the hydrophobic cavity was calculated to be ca. [2,7,14,17,18,23]. On the basis of this result, it was suggested that a ns-LTP isoform might be expressed specifically in root tissue [1,2,17].…”
Section: Modelling Of Pvr3 Proteinmentioning
confidence: 90%
“…As shown in Fig. 5A The PVR3 amino acid sequence was aligned with LTP from Arabidopsis [22], barley [9], brassica [8], broccoli [14], carrot [18], caster bean [25], gerbera [11 ], maize [20], spinach [1 ], tobacco [7], tomato [24], Vigna [12], and wheat [5] using the program CLU STAL. The amino acid residues are presented in standard one letter code.…”
Section: Modelling Of Pvr3 Proteinmentioning
confidence: 99%
“…Nuclease S1 protection was described previously [10]. A uniformly 32p-labelled probe (nt + 143 to -188), prepared using the same primer as above, was hybridized to 50/2g total RNA in 80~o formamide at 37 °C, digested with 60 units nuclease S1 (Boehringer, Mannheim).…”
Section: Determination Of Transcription Start Sitementioning
confidence: 99%
“…2,5,10,24,30]. However, there are relatively few reports on the expression of constitutively expressed genes.…”
Section: Introductionmentioning
confidence: 99%